Psychosocial stress induction in vivo vs. in virtuo and the influence of a health app on the acute stress reaction in youths: a study protocol for a randomized controlled trial - Daniel Schleicher; Angelika Ecker; Martin Kocur; Irina Jarvers; Colin Nash; Leonie Götz; Alexandra H. Otto; Stephanie Kandsperger; Romuald Brunner (Trials, 2022)
Abstract Background Acute and everyday stress is substantial for the development of mental and physical diseases, therefore it is crucial to get a better understanding of its pathogenesis. Different methods (e.g., Ambulatory Assessment) and stress reactivity paradigms (e.g., Trier Social Stress Test / TSST) in laboratory settings are often used to investigate basic mechanisms of this process. Due to the technological progress of the last years and especially due to children and adolescents growing up with it, the application of these developments in clinical research is reasonable. The aim of this project is to successfully transfer the TSST for children and adolescents into the virtual world, which will be compared to a real TSST situation. Physiological and psychological stress reactions will be analyzed in order to assess similarities and differences. Moreover, it will be investigated whether a Heart Coherence Exercise (HCE) has a stronger influence on coping with acute stress compared to Natural Relaxation (NR). Methods This single-center experimental study will examine acute and everyday stress and coping processes in eighty-four healthy children and adolescents between the ages of 11 and 17. For everyday stress, different parameters (e.g., hormonal profiles and mood ratings) as well as a history of stressful life events and utilized coping methods will be recorded and a relaxation exercise will be practiced on a smartphone over 2 days. Regarding the acute stress reaction, the participants will be confronted either with the virtual or the real version of the TSST, followed by the trained relaxation exercise (HCE vs. NR). Physiological (e.g., cortisol and heart rate) and psychological stress markers (e.g., mood and gaze behavior) will be recorded continuously. Discussion Studies are sparse using a virtual version of the TSST in children and adolescents. A successful virtual TSST would constitute an economical variant, which would also make it easier to administer it in clinical or population-based samples. Effective ambulatory relaxation exercises would be a useful addition to clinical treatment approaches. Trial registration The study is registered in the German Clinical Trials Register since 10 August 2020 ( DRKS00022063 ).